Efek Blueberry (Vaccinium sp.) Terhadap Kelembapan Kulit yang Terpapar Sinar Ultraviolet Akut - ADNYANA PUTRA, I GEDE AGUS DIVA; IDA AYU IKA WAHYUNIARI; NI MADE LINAWATI; I GUSTI KAMASAN NYOMAN ARIJANA (Hang Tuah Medical Journal, 2023)
Introduction: Maintained skin moisture is an indication of healthy skin. Acute UV exposure can cause sunburn, which is characterized by a loss of moisture in the skin. Polyphenol compounds are one practical approach to protecting the skin from sunburn so that skin moisture is maintained. Blueberries are one of the natural ingredients consists of anthocyanin compounds, which are polyphenols from the flavonoid group. Aims: To determine the effect of blueberries on skin moisture exposed to acute ultraviolet rays. Methods: Literature study using references in the form of research articles and literature reviews from national and international journals and related books published in the last 10 years. In writing this literature review, 42 references were used which were accessed through Google Scholar, NCBI, Crossref, and Pubmed. Results: Blueberries anthocyanins can maintain skin moisture from increased transepidermal water loss (TEWL) due to acute UV ray exposure by reducing the formation of UV stimulated reactive oxygen species (ROS) and lipid peroxidation in keratinocyte cells to maintain the elastic modulus and mechanical properties of keratinocytes as well as can prevent sunburn by reducing the skin's modulation of UV exposure. However, the absorption of anthocyanin compounds in the intestine is so low that taking blueberries orally alone is not enough to achieve good biodistribution. Conclusion: Blueberries affect retaining moisture in skin exposed to acute UV rays, so they have the potential to be used as skincare ingredients. However, further research needs to be done, especially to determine the side effects that can be caused and the required extract concentration.